1G5: a calmodulin-binding, vesicle-associated, protein kinase-like protein enriched in forebrain neurites - Godbout, M (J Neurosci, 1994)
We have characterized cDNA clones of 1G5, an mRNA highly enriched in the mammalian forebrain that encodes a 504-residue protein found in association with perikaryal membranes and neurites. The protein, which accumulates predominantly postnatally, is associated with vesicles in both axons and dendrites. The sequence of the 1G5 protein highly resembles those of protein kinases with serine/threonine specificity; however, although most residues universally conserved among protein kinases are present, a few signature residues are absent from the 1G5 protein. Furthermore, although recombinant 1G5 protein binds calmodulin in the presence of calcium, it lacks kinase activity with a sample substrate.